2018
DOI: 10.3389/fncel.2017.00434
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Analysis of mRNA and miRNA Expression of 3D-Cultured Neural Stem Cells (NSCs) in Spaceflight

Abstract: Recently, with the development of the space program there are growing concerns about the influence of spaceflight on tissue engineering. The purpose of this study was thus to determine the variations of neural stem cells (NSCs) during spaceflight. RNA-Sequencing (RNA-Seq) based transcriptomic profiling of NSCs identified many differentially expressed mRNAs and miRNAs between space and earth groups. Subsequently, those genes with differential expression were subjected to bioinformatic evaluation using gene onto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 79 publications
(81 reference statements)
0
14
0
Order By: Relevance
“…The culturing environment is one of the most important pivotal factors that in uence cell function and its potential therapeutic effects following transplantation. Our previous ndings demonstrated that NSCs tend to differentiate into neurons and that glial differentiation is inhibited during space ight [11].…”
Section: Discussionmentioning
confidence: 98%
“…The culturing environment is one of the most important pivotal factors that in uence cell function and its potential therapeutic effects following transplantation. Our previous ndings demonstrated that NSCs tend to differentiate into neurons and that glial differentiation is inhibited during space ight [11].…”
Section: Discussionmentioning
confidence: 98%
“…Neural stem cells isolated from rat telencephalon tissues cultured in an automated bioreactor onboard SJ-10 satellite maintained their potential and displayed a transcription profile similar to that of the control, but they tended to divide less and were more prone to enter neuronal differentiation [15]. Interestingly, neural stem cells exposed to microgravity tended to differentiate into astrocytes on transplantation [16].…”
Section: Introductionmentioning
confidence: 88%
“…To some extent, MG cells resemble neural stem cells [6], which have been studied in space conditions by other groups. Murine neural stem cells, cultivated in a 3D bioreactor in space, maintained their ''stemness,'' even displayed upregulation of stem cell transcription factors Sox2 and Pax6, but proliferated slower than in 1 g and underwent neural differentiation more readily [15]. Global transcriptomic analysis revealed the leading role of the WNT signaling pathway in these processes.…”
Section: Müller Gliamentioning
confidence: 99%
“…Our previous studies have demonstrated that the conditions in outer space promote neuronal differentiation of NSCs [9]. As microgravity is one of the key factors of outer space [10,11], this present study investigated the influence of simulated microgravity on three-dimensional (3D) cultured NSCs with a dynamic 3D Rotary Cell Culture System (RCCS).…”
Section: Introductionmentioning
confidence: 99%